SINTAKSA Learning Media Innovation as a Simulation of Correspondence and Digital Archiving Workflows to Enhance Student Engagement in Office Management - Nyoman Krisdiantoro; Andi Basuki; Erna Sukmawati (Transpublika Publisher, 2026)
The low student engagement in correspondence and archiving lessons within secondary vocational education, often exacerbated by digital device facility disparities, demands innovative, inclusive, and contextual learning media. This study aims to develop a digital simulation-based learning medium SINTAKSA (Sinergi Tata Kelola Surat dan Arsip) and evaluate its feasibility, practicality, and effectiveness in enhancing multidimensional student engagement. Using a Research and Development (R&D) method based on the systematic ADDIE model, this study involved 33 eleventh-grade Office Management students selected via purposive sampling. Data were collected using expert validation instruments, user practicality questionnaires, and a multidimensional student engagement scale measuring behavioral, emotional, and cognitive dimensions. The results demonstrated that the developed simulation media achieved high feasibility (83.75%) based on media and subject matter experts, and exceptional user practicality (93.71%). Crucially, student engagement significantly increased from a mean score of 71.84 to 84.01, with marked improvements in emotional (70.69 to 84.52), behavioral (71.55 to 83.57), and cognitive dimensions (73.28 to 83.94). These findings confirm that digital workflow simulations designed for multi-device accessibility can bridge infrastructural gaps, lower students’ cognitive load, and holistically elevate active learning behaviors in vocational education.